2021
DOI: 10.1136/bmjstel-2020-000707
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of preoperative tour to a simulated anaesthesia induction at operating theatre in reducing preoperative anxiety in children and their parents: a pragmatic, single-blinded, randomised controlled trial/ King Fahad Medical City

Abstract: ObjectiveTo evaluate the effectiveness of a preoperative tour to a simulated anaesthesia induction at operating theatre on reducing children’s and parents’ preoperative anxiety.DesignA pragmatic, single-centre, assessor-blinded, randomised controlled trial.SettingIn preoperative anaesthesia clinic and the operating room at a tertiary care centre in Saudi Arabia.ParticipantsOne hundred and sixteen children–parents dyads (pairs) (n=57) intervention group (IG); (n=59) control group (CG) with children aged 4–14 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, when the pediatric patients, who received and did not receive premedication, were compared, it was determined that the anxiety levels of the patients who received premedication were statistically significantly lower. Similar to our study, many studies have shown that premedication significantly reduces preoperative anxiety and prevents the development of postoperative behavioral disorders (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, when the pediatric patients, who received and did not receive premedication, were compared, it was determined that the anxiety levels of the patients who received premedication were statistically significantly lower. Similar to our study, many studies have shown that premedication significantly reduces preoperative anxiety and prevents the development of postoperative behavioral disorders (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…A T-test was performed on indicators that adhere to a normal distribution [8]: In cases where the data does not follow a normal distribution, T-test is not applicable, whereas Mann-Whitney U test does not rely on data distribution. Therefore, the Mann-Whitney U test [9] was conducted on indicators that do not obey the normal distribution:…”
Section: Selection Of Indicatorsmentioning
confidence: 99%